2016
DOI: 10.1159/000450894
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Fatigue May Be Associated with the Promoter Region of a <b><i>Monoamine Oxidase A </i></b>Gene Polymorphism

Abstract: Background: Post-stroke fatigue (PSF) is a common sequela of stroke. Despite reports of serotonergic involvement in the etiology of PSF, the potential contribution of serotonergic genes in the development of PSF needs to be investigated. Methods: A total of 373 patients, who experienced ischemic stroke for PSF, were evaluated 3 months after the stroke. PSF was assessed using the Fatigue Severity Scale. The genomic DNA collected and stored in a -70°C freezer was genotyped for 6 polymorphisms in genes associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…In one review, this is attributed to cultural differences in psychosocial factors rather than epidemiological determinants such as stroke type, though this review has found it to be a factor. 42 This is evident as our results show that most of the included studies in Asia have participants with only ischaemic stroke (n = 6), [31][32][33][50][51][52] whereas those in the Europe include patients with either both types of stroke (n = 11) or only haemorrhagic stroke (n = 4). [34][35][36]43,44,[47][48][49][53][54][55][56][57][58] A post-hoc sensitivity analysis supporting this demonstrates that studies in Europe that only included patients with ischaemic stroke have a similar PSF proportion to the ones conducted in Asia (37% vs 37%).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In one review, this is attributed to cultural differences in psychosocial factors rather than epidemiological determinants such as stroke type, though this review has found it to be a factor. 42 This is evident as our results show that most of the included studies in Asia have participants with only ischaemic stroke (n = 6), [31][32][33][50][51][52] whereas those in the Europe include patients with either both types of stroke (n = 11) or only haemorrhagic stroke (n = 4). [34][35][36]43,44,[47][48][49][53][54][55][56][57][58] A post-hoc sensitivity analysis supporting this demonstrates that studies in Europe that only included patients with ischaemic stroke have a similar PSF proportion to the ones conducted in Asia (37% vs 37%).…”
Section: Discussionmentioning
confidence: 76%
“…29,30 Most studies had a pre-specified aim to estimate fatigue prevalence except seven papers that focused on assessing the contributing factors of the condition. 21,[31][32][33][34][35][36] In terms of quality, the majority of studies had a medium to high-quality score of five or above out of nine (n = 20) (Figure 2). The most failed criterion was appropriate sampling as only two papers had a representative sample, with either a population-based or randomised sample, whereas the majority had a consecutive sampling.…”
Section: Resultsmentioning
confidence: 99%
“…The FSS has been validated in stroke patients [24], and based on previous studies, a cut-off score ≥4 was applied to indicate PSF [5, 25]. …”
Section: Methodsmentioning
confidence: 99%
“…Concerning the biological mechanisms of post-stroke fatigue, some studies proposed that the immune response after ischemic stroke may predict the occurrence of post-stroke fatigue ( 29 , 30 ). In Korean patients, it was found that post-stroke fatigue may be associated with genetic polymorphisms within the MAO-A gene in females ( 31 ). Hama et al showed that the monoamine neural network can be divided into catecholamine and serotonin branches, which are related to each other anatomically and functionally, and may affect the development of post-stroke fatigue and emotional disorders ( 14 ).…”
Section: Discussionmentioning
confidence: 99%